Effects of systemic ozone administration on the fresh extraction sockets healing: a histomorphometric and immunohistochemical study in rats - Miyasawa, Erton Massamitsu (2024)
Studies have highlighted numerous benefits of ozone therapy in the field of medicine and dentistry, including its antimicrobial efficacy against various pathogenic microorganisms, its ability to modulate the immune system effectively, reduce inflammation, prevent hypoxia, and support tissue regeneration. However, its effects on dental extraction healing remain to be elucidated. Objective: Therefore, this study aimed to evaluate the effects of systemically administered ozone (O3) at different doses in the healing of dental extraction sockets in rats. Methodology: To this end, 72 Wistar rats were randomly divided into four groups after extraction of the right upper central incisor: Group C – control, no systemic treatment; Group OZ0.3 – animals received a single dose of 0.3 mg/kg O3; Group OZ0.7 – a single dose of 0.7 mg/kg O3; and Group OZ1.0 – a single dose of 1.0 mg/kg O3, intraperitoneally. In total, six animals from each group were euthanized at 7, 14, and 21 days after the commencement of treatment. Bone samples were harvested and further analyzed by descriptive histology, histomorphometry, and immunohistochemistry for osteocalcin (OCN) and tartrate-resistant acid phosphatase (TRAP) protein expression. Results: All applied doses of O3 were shown to increase the percentage of bone tissue (PBT) after 21 days compared to group C. After 14 days, the OZ0.7 and OZ1.0 groups showed significantly higher PBT when compared to group C. The OZ1.0 group presented the most beneficial results regarding PBT among groups, which denotes a dose-dependent response. OCN immunostaining was higher in all groups at 21 days. However, after seven and 14 days, the OZ1.0 group showed a significant increase in OCN immunostaining compared to C group. No differences in TRAP+ osteoclasts were found between groups and time points. Conclusion: Therefore, O3 therapy at higher doses might be beneficial for bone repair of the alveolar socket following tooth extraction.